Dietary apigenin reduces LPS‐induced expression of miR‐155 restoring immune balance during inflammation. Issue 4 (23rd February 2015) - Arango, Daniel; Diosa‐Toro, Mayra; Rojas‐Hernandez, Laura S.; Cooperstone, Jessica L.; Schwartz, Steven J.; Mo, Xiaokui; Jiang, Jinmai; Schmittgen, Thomas D.; Doseff, Andrea I.
<x xml:space="preserve">Abstract</x> Scope High incidence of inflammatory diseases afflicts the increasing aging‐population infringing a great health burden. Dietary flavonoids, including the flavone apigenin, are emerging as important anti‐inflammatory nutraceuticals due to their health benefits, lack of adverse effects and reduced costs. MicroRNAs (miRs) play a central role in inflammation by regulating gene expression, yet how dietary ingredients affect miRs is poorly understood. The aim of this study was to identify miRs involved in the anti‐inflammatory activity of apigenin and apigenin‐rich diets and determine their immune regulatory mechanisms in macrophages and in vivo. Methods and results A high‐throughput quantitative reverse transcriptase PCR screen of 312 miRs in macrophages revealed that apigenin reduced LPS‐induced miR‐155 expression. Analyses of miR‐155 precursor and primary transcript indicated that apigenin regulated miR‐155 transcriptionally. Apigenin‐reduced expression of miR‐155 led to the increase of anti‐inflammatory regulators forkhead box O3a and smooth‐muscle‐actin and MAD‐related protein 2 in LPS‐treated macrophages. In vivo, apigenin or a celery‐based apigenin‐rich diet reduced LPS‐induced expression of miR‐155 and decreased tumor necrosis factor α in lungs from LPS‐treated mice. Conclusion These results demonstrate that apigenin and apigenin‐rich diets exert effective anti‐inflammatory activity in vivo by reducing LPS‐induced expression of miR‐155, thereby restoring immune balance.